STAT1a and STAT1b of black carp play important roles in the innate immune defense against GCRV. Issue 87 (April 2019) - Wu, Hui; Zhang, Yinyin; Lu, Xingyu; Xiao, Jun; Feng, Pinghui; Feng, Hao
Abstract: Signal transducer and activator of transcription 1 (STAT1) plays an important role in the Janus kinase (JAK)-STAT signaling of human and mammals; however, the mechanism of STAT1 in innate immune activation of teleost fishes remains largely unknown. In this study, two STAT1 homologues ( bcSTAT1a and bcSTAT1b ) of black carp ( Mylopharyngodon piceus ) have been cloned and characterized. Both bcSTAT1a and bcSTAT1b transcription in host cells was obviously increased in response to the stimulation of poly (I:C), lipopolysaccharide (LPS), grass carp reovirus (GCRV) and interferon (IFN); however, the increase rate of bcSTAT1b transcription post stimulation was obviously higher than that of bcSTAT1a . bcSTAT1a and bcSTAT1b were distributed in both cytoplasm and nucleus in the immunofluorescence staining assay. Self-association of bcSTAT1a and bcSTAT1b, and the interaction between bcSTAT1a and bcSTAT1b have been detected through co-immunoprecipitation (co-IP) assay; and the data of native polyacrylamide gel electrophoresis (PAGE) implied that bcSTAT1a and bcSTAT1b might form homodimer and heterodimer in vivo like their mammalian counterparts. Both bcSTAT1a and bcSTAT1b presented IFN-inducing ability in report assay, and both bcSTAT1a and bcSTAT1b showed antiviral activities against GCRV in EPC cells. Our data support the conclusion that both bcSTAT1a and bcSTAT1b play important roles in host antiviral innate immune activation initiated by GCRV. Highlights: bcSTAT1b transcription level was much higher than bcSTAT1a post stimulation. bcSTAT1a interacted with bcSTAT1b. Both bcSTAT1a and bcSTAT1b presented antiviral activity.